2007
DOI: 10.1111/j.1365-294x.2007.03597.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Earth's largest fish, the whale shark (Rhincodon typus)

Abstract: Large pelagic vertebrates pose special conservation challenges because their movements generally exceed the boundaries of any single jurisdiction. To assess the population structure of whale sharks (Rhincodon typus), we sequenced complete mitochondrial DNA control regions from individuals collected across a global distribution. We observed 51 single site polymorphisms and 8 regions with indels comprising 44 haplotypes in 70 individuals, with high haplotype (h = 0.974 +/- 0.008) and nucleotide diversity (pi = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
163
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(190 citation statements)
references
References 72 publications
17
163
2
6
Order By: Relevance
“…Unlike terrestrial and freshwater species that frequently exhibit strong population genetic structure from barriers to gene flow such as rivers, waterfalls, mountains, and deserts, marine species typically experience fewer and less formidable physical obstacles. While some species are restricted by habitat requirements or feeding habits (e.g., tropical reef fishes) and show clear population genetic structure (Shulman & Bermingham, 1995), pelagic species often have wide distributions, large population sizes, high fecundity, and extensive gene flow (Palumbi, 1992), and tend to display weak population structure in the absence of natal philopatry (Carr, Duggan, Stenson, & Marshall, 2015; Castro et al., 2007; Vis, Carr, Bowering, & Davidson, 1997; Ward, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…Unlike terrestrial and freshwater species that frequently exhibit strong population genetic structure from barriers to gene flow such as rivers, waterfalls, mountains, and deserts, marine species typically experience fewer and less formidable physical obstacles. While some species are restricted by habitat requirements or feeding habits (e.g., tropical reef fishes) and show clear population genetic structure (Shulman & Bermingham, 1995), pelagic species often have wide distributions, large population sizes, high fecundity, and extensive gene flow (Palumbi, 1992), and tend to display weak population structure in the absence of natal philopatry (Carr, Duggan, Stenson, & Marshall, 2015; Castro et al., 2007; Vis, Carr, Bowering, & Davidson, 1997; Ward, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…However, genetic analysis contradicts assumptions of panmixia in some species, e.g. narrow-barred Spanish mackerel Scomberomorus commerson (Sulaiman & Ovenden 2010), Atlantic bluefin tuna Thunnus thynnus (Boustany et al 2008, Riccioni et al 2010) and whale shark Rhincodon typus (Castro et al 2007). Some marine species range widely to feed; during this phase, individuals of the same species will be admixed, spatial genetic population subdivision will be minimal and gene flow will be assumed to be high.…”
Section: Introductionmentioning
confidence: 99%
“…Cobia is well known for hitchhiking on large marine animals and migrating to long distances on its own (Shaffer and Nakamura 1989). Population genetic studies on whale sharks, a frequently observed hitchhiking host of cobia, have shown that whale shark migrations can cover vast distances (as much as 13,000 km) and that their population shows no marked structure between the Indian and Pacific Oceans (Castro et al 2007;Schmidt et al 2009). This behavior of cobia therefore has the potential to increase its migration range to include geographic regions separated by vast distances.…”
Section: Tests On Population Differentiation Based On Geographic Locamentioning
confidence: 99%